Economic Planning and Poverty Alleviation Strategies in Nepal - Chaudhary, Manoj Kumar (Research Nepal Journal of Development Studies, 2018)
Nepal is a developing country in the world. It has a lot of problems for the rapid development in present context. Economic planning was started in 1930s’ decade from former U.S.S.R so that their economy was not highly affected by the great depression of that decade. In Nepal, 2013 B.S first five-year plan was formulated and implemented. Poverty alleviation is the main objective of economic plans of Nepal since 7th plan. The study identifies the major issues of poverty alleviation strategies of Nepal. Methodologically secondary sources are used to analyze the five-year plans since the beginning. Most of the strategies were concerned with the formation of better and prosperous country with higher living standard of its citizen. Direct and indirect measures are taken from the side of government, private sector and co- operative, but the achievement is not so remarkable. Lack of domestic resources, low rate of capital formation, depend on foreign sources, lack of political commitment, low level of awareness are the causes of failure of poverty alleviation strategies in Nepal.